2015
DOI: 10.1051/0004-6361/201527563
|View full text |Cite
|
Sign up to set email alerts
|

Large dust grains in the wind of VY Canis Majoris

Abstract: Massive stars live short lives, losing large amounts of mass through their stellar wind. Their mass is a key factor determining how and when they explode as supernovae, enriching the interstellar medium with heavy elements and dust. During the red supergiant phase, mass-loss rates increase prodigiously, but the driving mechanism has proven elusive. Here we present high-contrast optical polarimetric-imaging observations of the extreme red supergiant VY Canis Majoris and its clumpy, dusty, mass-loss envelope, us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 29 publications
3
54
2
Order By: Relevance
“…In recent years, however, there is increasing observational evidence for the existence of such large particles in the close vicinity of AGB stars and supergiants (e.g. Norris et al 2012;Scicluna et al 2015;Ohnaka et al 2016). Furthermore, detailed atmosphere and wind models based on this mechanism show good agreement with observations regarding mass loss rates and wind velocities, as well as visual and near-IR colors, and their variation with pulsation phase (Bladh et al 2013(Bladh et al , 2015.…”
Section: Introductionmentioning
confidence: 68%
“…In recent years, however, there is increasing observational evidence for the existence of such large particles in the close vicinity of AGB stars and supergiants (e.g. Norris et al 2012;Scicluna et al 2015;Ohnaka et al 2016). Furthermore, detailed atmosphere and wind models based on this mechanism show good agreement with observations regarding mass loss rates and wind velocities, as well as visual and near-IR colors, and their variation with pulsation phase (Bladh et al 2013(Bladh et al , 2015.…”
Section: Introductionmentioning
confidence: 68%
“…In our analysis, we also include that observations of polarized visible light obtained with Hubble ) and SPHERE/VLT (Scicluna et al 2015) show that the polarization vectors seen towards clump C in visible wavelengths are roughly perpendicular to those observed at mm wavelength presented here.…”
Section: Dust Polarization Of Clump Cmentioning
confidence: 87%
“…Examples include IRC +10 216 and OH 26.5, which were fitted with MoD code by Groenewegen et al (2012) and Groenewegen (2012), respectively. Recently, Norris et al (2012), Scicluna et al (2015), and Ohnaka et al (2016) found evidence for grains in the range 0.3-0.5 µm, and 0.1-1 µm grains are advocated to drive the outlow around oxygen-rich stars (Höfner 2008, Bladh & Höfner 2012). …”
Section: Dust Grain Propertiesmentioning
confidence: 99%